Comparison between scot and CBDP techniques in assessment genetic diversity and variation of two populations of bigfin reef squid (Sepioteuthis lessoniana d’Orbigny) in Con Dao and Phu Quoc islands, Vietnam - Le , Ngoc Trieu; Thai, Thach Bich; Nguyen, Van Long (Academia Journal of Biology, 2024)
The Start Codon Targeted Polymorphism (SCoT) and CAAT box-derived polymorphism (CBDP) techniques were used to analyze the genetic diversity and variation of two bigfin reef squid populations in waters surrounding the Con Dao and Phu Quoc islands of Vietnam for technical comparison. The two used techniques reflected different levels of pairwise genetic similarity among individuals depended on the investigated population. Gene differentiation (GST) between the two investigated populations was 0.0767 and 0.0373 leaded to the genetic distance between them was 0.0381 and 0.0228, and the gene flow was Nm = 6.0195 and 12.9061 migrants per generation between the populations based on SCoT and CBDP techniques, respectively. Genetic variation within individuals of both populations (WP) played the key role in the total genetic variation of whole species in surveyed geographic regions with the distribution of 91.44% based on SCoT data and 93.76% based on CBDP data, the distribution of genetic variation among populations (AP) was small. For whole species in the surveyed region, the CBDP markers showed higher genetic diversity, while the SCoT markers reflected the differentiation and genetic distance between the two investigated populations better. Overall, the abilities to detect polymorphisms and the number of revealed loci using SCoT markers were better than using CBDP markers, while the ability to distinguish samples and the primer combination to detect the differences among investigated samples using CBDP markers were better than using SCoT markers, and the overall utility was comparable between these two marker systems. The results from this study prove that the CBDP technique can also be used in studies of animal population genetics.